2021
DOI: 10.3389/fnins.2021.634666
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Diseases Among Norwegian LRRK2 Mutation Carriers. A 15-Years Follow-Up of a Cohort

Abstract: The first families with LRRK2 related Parkinson’s disease (PD) were presented around 15 years ago and numerous papers have described the characteristics of the LRRK2 phenotype. The prevalence of autosomal dominant PD varies around the world mainly depending on local founder effects. The highest prevalence of LRRK2 G2019S PD in Norway is located to the central part of the country and most families could be traced back to common ancestors. The typical Norwegian LRRK2 phenotype is not different from classical PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Interestingly several genes associated with RA genetic predisposition were also differentially expressed in the IFITM3+ monocytes subsets such as HLA-DQB1, LRRK2, TLE3. LRRK2 mutations have been associated with several auto-immune diseases and especially rheumatoid arthritis predisposition (46,47). In addition, a meta-analysis demonstrated that HLA-DQB1 polymorphisms were associated with RA with a protective role of DQB1*02 and DQB1*06 and conversely a susceptibility role of DQB1*04 (48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly several genes associated with RA genetic predisposition were also differentially expressed in the IFITM3+ monocytes subsets such as HLA-DQB1, LRRK2, TLE3. LRRK2 mutations have been associated with several auto-immune diseases and especially rheumatoid arthritis predisposition (46,47). In addition, a meta-analysis demonstrated that HLA-DQB1 polymorphisms were associated with RA with a protective role of DQB1*02 and DQB1*06 and conversely a susceptibility role of DQB1*04 (48).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS identified a variant in LRRK2 that conferred an increased risk for Crohn’s disease [ 79 ] – an inflammatory bowel disease. Moreover, in Norwegian LRRK2 families a high incidence of rheumatoid arthritis was reported [ 80 ]. Consistent with elevated LRRK2 levels in B cells, T cells [ 81 ], macrophages [ 82 ], monocytes and neutrophils [ 71 ], the kinase is thought to regulate the immune response to pathogens [ 83 ].…”
Section: Cellular Function Of Lrrk2mentioning
confidence: 99%
“… 12 , 13 The discovery of LRKK2 gene as a major susceptibility factor for Parkinson's disease in 2004, 14 , 15 activated the research in this area as a potential mechanism to therapeutically target this disease. Recently, there have been several associations of this enzyme to processes of inflammation that could contribute to Parkinson's or other diseases, including MS. 16 In addition, LRKK2 may contribute not only to inflammation processes but also to neurotoxic processes involved in neurodegenerative disorders 17 and thus may be a key player in the progression of neurodegenerative pathologies. 18 The relevance of LRRK2 for neurogenesis in the adult CNS, neurite outgrowth, and the formation of axons and dendrites is also known.…”
Section: Introductionmentioning
confidence: 99%